Cenozoic crustal thickness variations and surface uplift in the southeastern Tibetan Plateau: Insights from detrital zircon trace elements in the Gongga Shan region - Zhao, Yanglin; Shen, Xiaoming; He, Zhiyuan; Wu, Xiong; Jia, Yingying; Tang, Xiudang (Lithos, 2024)
The timing and mechanism of uplift in the southeastern Tibet Plateau have long been subjects of debate. The Gongga Shan region, positioned at the convergence of the Songpan-Ganzi, Chuandian, and Yangtze blocks, serves as a crucial vantage point for unraveling the evolutionary history of the southeastern Tibet Plateau. Nevertheless, the uplift history of the Gongga Shan region remains shrouded in uncertainty. By employing multivariate trace element ratios and reconstructing crustal thickness using zircon Eu/Eu*, our research has unveiled distinct periods of crustal thickening and thinning events. Within the time span of ∼240–160 Ma, a discernible thickening trend emerged from ∼35 to ∼45 km between ∼240 and ∼ 215 Ma, followed by a relatively stable phase from ∼215 to ∼170 Ma, and subsequently a decline from ∼170 to ∼160 Ma, reducing the thickness from ∼45 to ∼30 km. In the period from ∼55 to ∼5 Ma, an initial increase in thickness occurred from ∼30 to ∼60 km between ∼55 and ∼ 30 Ma, succeeded by an overall thinning from ∼60 to ∼35 km between ∼30 and ∼ 10 Ma. Moreover, based on our reconstructed crustal thickness data, we have traced the paleo-elevation changes in the Gongga Shan region from the Cenozoic to the present, revealing a fluctuation from ∼0.5 to ∼4.5 km. We attribute the Triassic-Jurassic crustal thickening and subsequent thinning to the Triassic orogeny and post-collision extension following the closure of the Paleo-Tethys Ocean. Our findings further suggest that during the Eocene-Oligocene period, the Gongga Shan region experienced significant crustal thickening and surface uplift, indicative of intense compression. This phenomenon likely resulted from the northeast-directed compression of the Indian-Eurasian plate, causing substantial crustal shortening and thickening in specific areas of the southeastern Tibet Plateau, leading to rapid surface uplift. Subsequently, during the Oligocene-Miocene, the detachment and subsidence of the lithospheric mantle triggered rapid crustal thinning in the Gongga Shan region. This phase was accompanied by relatively stable and slight surface uplift, signifying a shift in the plateau uplift mode of the southeastern Tibet Plateau from compression to lateral extrusion. •959 new detrital zircon trace elements data from the Gongga Shan are reported.•Zircon Eu/Eu* shows significant crustal thickening occurred between ∼55 and ∼ 30 Ma.•Paleo-elevation reconstruction reveals ∼4 km of plateau growth in the Cenozoic.